Same same but different?: 12/14 stem and head tapers in total hip arthroplasty - Müller, Ulrike; Braun, Steffen; Schröder, Stefan; Sonntag, Robert; Kretzer, Jan Philippe (The journal of arthroplasty, 2017)
Background: Taper corrosion has been identified to be a major concern in total hip arthroplasty during the past years. So far, the mechanisms that lead to taper corrosion in modular taper junctions are not fully understood. However, it has been shown that corrosion is also influenced by the geometry and topography of the taper, and these parameters vary among the implant manufacturers. The purpose of this study was to investigate the variations of common stem and head tapers regarding design and surface characteristics. Methods: An analysis of selected commercially available 12/14 stem and head tapers was performed. As geometric parameters, the taper angle, the opening taper diameter, and the taper length were measured using a coordinate measuring machine. Several topographic parameters were determined using a tactile roughness measurement instrument. Results: Although all investigated tapers are so-called 12/14 tapers, this study showed that the stem and head tapers differ among the manufacturers. The stem tapers were clearly different in both geometry and topography, and the range in variation of the topographic parameter was greater than it was for the geometric parameter. In contrast, the head tapers were different in their geometry, although not in topography. Conclusion: Ultimately, this study provides an overview on the characteristics and variations of modular hip taper connections, and in addition, a new classification system regarding the surface finish is presented. These findings could be further considered in experimental corrosion or retrieval studies.